Knowledge and perceptions on toxoplasmosis among pregnant women and nurses who provide prenatal in primary care - Sousa, Jayra Adrianna da Silva (2017)
Background Toxoplasmosis is an infection that affects almost a third of the world population. In adults, it is often asymptomatic, although having important manifestation in children- infected by placental transmission. The prenatal is an important moment, requiring actions in women’s care during pregnancy, in order to prevent diseases that could compromise the mother and the child’s life. Methods This is a descriptive study of qualitative approach aimed to understand the perception of nurses and pregnant women about toxoplasmosis during primary – prenatal care. The study was conducted in five selected primary health care units, in the municipality of São Luis - MA. The sample consisted of 15 nurses working in nursing consultation and 15 pregnant women attended in prenatal care. For data collection, a semi-structured questionnaire and an interview guide covering issues related to knowledge and conduct on toxoplasmosis were used. For analysis, the content analysis technique was used. Results The answers were transcribed, organized and grouped thematically, where the following categories emerged: knowledge about examination requests; knowledge about toxoplasmosis; guidance during prenatal consultation; knowledge of nurses about the avidity test; procedures and guidelines on reagent cases. Pregnant women showed unawareness about toxoplasmosis and its effects. Nurses, although having basic knowledge about the subject, showed little applicability regarding pregnant women’s guidance. Conclusion The nurse plays an important role in educational activities regarding pregnant women, contributing to the quality of prenatal care. Pregnant women were shown to have some knowledge about toxoplasmosis, although they said they did not have assurance about prevention.